Involvement of Low‐Density Lipoprotein Receptor in the Pathogenesis of Pulmonary Hypertension. Issue 2 (21st January 2020) - Umar, Soban; Ruffenach, Gregoire; Moazeni, Shayan; Vaillancourt, Mylene; Hong, Jason; Cunningham, Christine; Cao, Nancy; Navab, Sara; Sarji, Shervin; Li, Min; Lee, Lisa; Fishbein, Greg; et al.
Abstract : Background: Recently, we and others have reported a causal role for oxidized lipids in the pathogenesis of pulmonary hypertension (PH). However, the role of low‐density lipoprotein receptor (LDL‐R) in PH is not known. Methods and Results: We examined the role of LDL‐R in the development of PH and determined the efficacy of high‐density lipoprotein mimetic peptide 4F in mitigating PH. Explanted human lungs and plasma from patients with PH and control subjects were analyzed for gene expression, histological characteristics, and lipoprotein oxidation. Male LDL‐R null (LDL‐R knockout) mice (12–15 months old) were fed chow, Western diet (WD), WD with 4F, and WD with scramble peptide for 12 weeks. Serial echocardiography, cardiac catheterization, oxidized LDL assay, real‐time quantitative reverse transcription–polymerase chain reaction, and histological analysis were performed. The effect of LDL‐R knockdown and oxidized LDL on human pulmonary artery smooth muscle cell proliferation was assessed in vitro. LDL‐R and CD36 expression levels were significantly downregulated in the lungs of patients with PH. Patients with PH also had increased lung lipid deposits, oxidized LDL, E06 immunoreactivity, and plasma oxidized LDL/LDL ratio. LDL‐R knockout mice on WD developed PH, right ventricular hypertrophy, right ventricular dysfunction, pulmonary vascular remodeling, fibrosis, and lipid deposition in lungs, aortic atherosclerosis, and left ventricular dysfunction, which were prevented by 4F. Interestingly, PH in WD group preceded left ventricular dysfunction. Oxidized LDL or LDL‐R knockdown significantly increased proliferation of human pulmonary artery smooth muscle cells in vitro. Conclusions: Human PH is associated with decreased LDL‐R in lungs and increased oxidized LDL in lungs and plasma. WD‐fed LDL‐R knockout mice develop PH and right ventricular dysfunction, implicating a role for LDL‐R and oxidized lipids in PH.